Kinerja Keuangan: Analisis Laporan Arus Kas Pada CV Alymar Lestari Konsultan - Longginus Gelatan; Vebi Vebi (STIE Jambatan Bulan, 2022)
This study aims to determine the financial performance of CV Alymar Lestari Consultant based on the analysis of the company's cash flow statements. The method used is descriptive method. This analysis begins by collecting data from CV Alymar Lestari Consultan, then managing the data that has been collected by calculating the company's cash flow report by calculating the analysis of Cash return on sales ratio, Cash Flow to net income and Cash reinvestment ratio. The results of this study indicate that the company's financial performance is quite good